OPTIMAL METHODS OF THERAPEUTIC MODULATION OF THE NASAL NERVES - Madaminova Nigora Ergashevna (Western European Studies, 2024)
This annotation offers a comprehensive overview of the therapeutic strategies aimed at modulating nasal nerves to address various nasal-related conditions. It delves into the intricate network of nasal nerves and their roles in sensory perception, regulation of nasal airflow, and immune responses. The annotation reviews current pharmacological interventions, including nasal sprays, antihistamines, and corticosteroids, highlighting their mechanisms of action and clinical efficacy in managing conditions such as rhinosinusitis, allergic rhinitis, and nasal congestion.
Keywords: efficacy; congestion; rhinitis